In defense of the no discharge after notice rule: A reply - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2010)
Mr Trukhtanov has made his own summary of and response to my own account of equitable (and statutory) assignment, and how notice of assignment operates within them. Having been reminded of how the cases on the topic are usually understood, readers will have to make up their own minds. While there is, always, room for further thought, it is important not to lose sight of two fairly important distinctions. Where A is the debtor, B is the creditor, and C is an assignee to whom B has assigned the chose in action arising from A’s debt obligation, a distinction should be drawn between: the question to whom the debtor is liable; and what the debtor is obliged to do to be discharged from that debt obligation. A distinction should also be drawn between cases where A has paid B in satisfaction of the contractual promise (thus discharging the contractual obligation by precise performance) and cases where A has not.